“[...] nós aqui é o espaço dos sem vez” - quilombolas e educação em Poconé/MT - Moreira, Nilvaci Leite de Magalhães (2019)
This article deals with families and schools in quilombola communities and aims to understand the perception of quilombola families in relation to schooling and to identify how the strategies used to ensure access and permanence of children in the educational environment. The research was carried out in the quilombola communities of Jejum, Laranjal e Curralinho, belonging to the municipality of Poconé, state of Mato Grosso, Brazil. The data used in the study were analyzed through qualitative analysis, based on field research, interviews with 14 families and in-depth observation, which allowed the development of an ethnographic study. The results were analyzed from concepts such as culture, education, quilombo, community and identities, as a way to understand how quilombola families imagined an idea of school and its importance in their children’s lives. It is concluded that families show concern about schooling and, even in situations of vulnerability and denial of social rights advocated for all Brazilian citizens by the Federal Constitution of 1988, they use alternative methods to ensure the education of their children. It is noticed that families recognize and value a school, however, they develop a process of their own education, focused on reciprocal, common and mutual respect, or one that is passed on from generation to generation. Such process provides the social actors involved with the recognition of participation and preservation of cultural traits that permeate life in the community. The study also points out how social policies aimed at these families are not being effectively carried out, being subject to a biased selection of only a few communities to benefit from the actions, precariously, in order to give to society an answer claiming that black people do not face the same problems of the past.